Dampak Penyeludupan Barang Ilegal dari Filipina ke Indonesia Melalui Sulawesi Utara dari Prespektif Human Security - Mikhael Samuel Benaya Taaluruga; Roberto Octavianus Cornelis Seba; Indra Wisnu Wibisono (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze the dynamics of illegal goods smuggling from the Philippines to Indonesia via North Sulawesi and its impact on human security. The study employed a descriptive qualitative approach with a literature review method utilizing scientific journals, international agency reports, government documents, and other official sources. The analysis was conducted using Transnational Organized Crime Theory and the concept of Human Security. The results indicate that smuggling exploits the geographic conditions of border areas, cross-border socio-economic relations, and weak maritime surveillance through the use of small vessels and organized criminal networks. This activity impacts economic security through state losses, unfair business competition, and disruption to the local economy. It also impacts personal security due to the influx of firearms, hazardous materials, and the increased risk of community involvement in criminal networks. The study concludes that smuggling constitutes a non-traditional security threat that requires strengthened maritime surveillance, bilateral cooperation, and the empowerment of border communities.